A construção de pedagogias decoloniais nos currículos das escolas indígenas - José Licínio Backes (EccoS – Revista Científica)
This paper argues that Indigenous schools have been constructing intercultural curricula and decolonial pedagogies. It is based on both interculturality theorists and a field research carried out with Indigenous students, all of them with a master’s degree in education. Data were obtained from both semi-structured interviews with indigenous people in the second half of 2017, with a focus on Terena, Guarani and Tuyuca ethnicities, and analysis of these subjects’ dissertations. From the research, it is possible to conclude that the construction of curricula and decolonial pedagogies is mainly based on both the strong bond the Indigenous students keep with their communities and the perspective that difference between knowledges do not necessarily mean hierarchization and disqualification, but it may mean complementarity.